Optimal Linear Precoder Design for Space-Time Block Coded Systems - Zhenshan Zhao; Guozhi Xu (2006 International Conference on Wireless Communications, Networking and Mobile Computing, 2006)
Taking the pairwise error probability (PEP) as the performance criterion and exploiting the channel covariance information at the transmitter, this paper studies the optimal linear precoder design of the correlated multiple-input multiple-output (MIMO) wireless system. The precoder can be used along with any space-time block codes (STBC), which is an extension of Y. Zhao et al. (2004) . The optimal beamforming direction of the precoder is proved to match the structure of STBC and transmit correlation matrix. The optimal power allocation scheme is related to transmit correlation matrix, receive correlation matrix and STBC. The quasi-orthogonal space-time block codes (QSTBC) is taken as an illustration to investigate the performance of the optimal precoder